Cross-cultural studies on organizational strategies for shipping firms : aspect of individualism or collectivism, power distance and performance orientation - Wong, Sek Teng. (2013)
More than 90 per cent of the world trade is carried by maritime transport and thus shipping is essential for the growth of economy. However, many shipping companies were negatively affected by the financial crisis. Singapore shipping companies also cannot escape from the disaster in shipping industry. In order to survive in this industry, the traditional shipping companies need to have a change to adapt the new trend. Hence, impacts of the culture on the implementation of strategy were widely discussed in this report.